2011
DOI: 10.1016/j.molcel.2011.06.031
|View full text |Cite
|
Sign up to set email alerts
|

RNA Homeostasis Governed by Cell Type-Specific and Branched Feedback Loops Acting on NMD

Abstract: SUMMARY Nonsense-mediated mRNA decay (NMD) is a conserved RNA decay pathway that degrades aberrant mRNAs and directly regulates many normal mRNAs. This dual role for NMD raises the possibility that its magnitude is buffered to prevent the potentially catastrophic alterations in gene expression that would otherwise occur if NMD were perturbed by environmental or genetic insults. In support of this, here we report the existence of a negative feedback regulatory network that directly acts on seven NMD factors. Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
271
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 200 publications
(307 citation statements)
references
References 67 publications
31
271
2
1
Order By: Relevance
“…1E). These results correlate with previous observations, referred to as feedback regulation 32 or autoregulation. 33 Finally, RNA-seq tags were piled up on the last exon of the RPL12 transcript variant 2, a known NMD target, 50 in response to UPF1 knockdown, indicating that the splicing variant recognized by NMD had escaped from degradation in response to UPF1 depletion (Fig.…”
Section: Resultssupporting
confidence: 93%
“…1E). These results correlate with previous observations, referred to as feedback regulation 32 or autoregulation. 33 Finally, RNA-seq tags were piled up on the last exon of the RPL12 transcript variant 2, a known NMD target, 50 in response to UPF1 knockdown, indicating that the splicing variant recognized by NMD had escaped from degradation in response to UPF1 depletion (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Therefore the situation appears analogous to what occurs in higher eukaryotes in which such introns can trigger EJC-mediated NMD. NMD control of N. crassa upf1 mRNA stability might be exerted through recognition of its uORF stop codons as PTCs, as is the case for N. crassa arg-2 ( Figure 5A) and S. cerevisiae CPA1 (Gaba et al 2005), or through its relatively long 39-UTR ( Figure 1A) as is reported for metazoan UPF1 (Huang et al 2011;Longman et al 2013), but this remains to be determined.To our knowledge, this work represents the first demonstration of circuits that enables regulation at the level of mRNA stability for eRF1, eIF4a3, and Y14. Autoregulation of mRNA levels for NMD factors has been reported for metazoans (Huang et al 2011;Yepiskoposyan et al 2011; reviewed in Karam et al 2013;Longman et al 2013) and autoregulation of NMD and EJC factors has been reported for plants (Nyiko et al 2013).…”
mentioning
confidence: 81%
“…3A). To test whether Rhox10 escapes MSCI, we assayed Rhox10 pre-mRNA level, as several studies have used pre-mRNA levels as a reliable measure of gene transcription rate (Imam et al 2009, Huang et al 2011. qRT-PCR analysis revealed that while Rhox10 pre-mRNA is extremely high in both undifferentiated type A spermatogonia and differentiating type A spermatogonia (type A 1-4 spermatogonia), its level drops sharply in all the more mature germ cell subsets, including pachytene spermatocytes, where MSCI occurs (Fig.…”
Section: Transcriptional Control Of Rhox10mentioning
confidence: 99%